Pengaruh Daya Tarik Iklan dan Kualitas Produk terhadap Minat Beli Konsumen Eiger di Kota Tasikmalaya - Tatiek Taufika Nurjanah Saputri (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This study aims to determine the effect of advertising attractiveness and product quality on consumer buying interest in Eiger in Tasikmalaya City (Survey of Visitors of Eiger Partners in Tasikmalaya City). The method used in this study is causality through a survey approach. With a research sample of 100 visitors of Eiger Partners in Tasikmalaya City. The data used is primary data. The analytical tool used in this study is multiple regression using SPSS 26.0. The results showed that the attractiveness of advertising and product quality had a significant influence on the buying interest of Eiger Partners in the City of Tasikmalaya. Partially, Advertising Attractiveness has a significant influence on the Buying Interest of Eiger Partners in Tasikmalaya City. Partially, product quality has a significant influence on the buying interest of Eiger Partners in Tasikmalaya City